2007
DOI: 10.2355/isijinternational.47.1168
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Precipitation During Intercritical Annealing in Cold Rolled TRIP Steels

Abstract: Flat carbon steel manufacturers are currently developing new TRansformation Induced Plasticity (TRIP) steels as a response to strong demands for vehicle lightening and security reinforcement from the automobile sector. Compared to conventional high strength steels these advanced grades exhibit a very favourable compromise between strength and ductility and can therefore be produced in thinner, lighter gauge strips with equivalent functional properties. The excellent mechanical properties of TRIP steels are att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 10 publications
4
14
0
2
Order By: Relevance
“…However, due to the small effect on the mechanical properties this was not checked. [33], the solubility of V in austenite is such that there will be little or no V precipitation during hot rolling and coiling as long as the coiling temperature is kept below *500 8C. This is confirmed by the low concentration of precipitated V measured in the hot bands (Table 4b) and also by TEM investigations on thin foils taken from hot strips.…”
Section: Cold Stripssupporting
confidence: 61%
“…However, due to the small effect on the mechanical properties this was not checked. [33], the solubility of V in austenite is such that there will be little or no V precipitation during hot rolling and coiling as long as the coiling temperature is kept below *500 8C. This is confirmed by the low concentration of precipitated V measured in the hot bands (Table 4b) and also by TEM investigations on thin foils taken from hot strips.…”
Section: Cold Stripssupporting
confidence: 61%
“…However, in addition to RA, multiple phases are usually present in TRIP steels due to the thermomechanical processing, which renders the deformation of TRIP steels very complicated. So far great effort was devoted to optimizing the thermomechanical processing parameters for improved mechanical properties, [10][11][12][13][14] but the influence of strain-induced martensitic transformation in TRIP steels on the work-hardening behavior was not well understood. In particular, the micromechanical character of individual phase on the work-hardening process in TRIP steels was far from being well explored due to the complexity from the multiple phases.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the spherical VC precipitates disperse at the phase interfaces and they effectively pin the interfaces so that they cannot move. The VC precipitates are mainly precipitated at low temperature (FCC → BCC phase transformation) and prevent the austenite grains coarsening and improve the strength of the steel . However, the carbides at the phase interfaces can decrease the plasticity and toughness of the steel .…”
Section: Discussionmentioning
confidence: 99%